Students' Knowledge gains, Self-efficacy, Perceived Level of Engagement, and Perceptions with regard to Home-based Biology Experiments (HBEs) - Robledo, Dave Arthur; Miguel, Frosyl; Arizala-Pillar, Genevieve; Errabo, Denis Dyvee; Cajimat, Rodney; Prudente, Maricar; Aguja, Socorro (Journal of Turkish Science Education, 2023)
Home-based biology experiments (HBEs) are practical learning guides that allow students to perform safe and appropriate experiments at home. This quasi-experimental study aimed to determine students’ perceptions, knowledge gains, self-efficacy, and engagements on the use of HBEs. Ten teacher-collaborators and 836 students participated in the implementation. Teacher-made parallel tests and 38-item perceptions, self-efficacy, and engagement questionnaires were distributed via Google Forms. Results revealed that most participants agreed that HBEs were lesson congruent, risk-free, the materials were readily available, and it was fun and challenging. Furthermore, HBEs were found to be effective in improving students’ knowledge gains (g=0.68), perceptions (x=3.56), self-efficacy (x=3.36), and engagements (x=3.45). Factors such as grade level, gender, and type of HBEs also influenced the dependent variables. The study concluded that home-based biology experiments are relevant teaching material to deliver practical learning among students in a distance learning modality.
Keywords: Home-based Biology Experiments; Perceptions; Self-efficacy; Engagements